High-resolution mapping and terrain classification of Halimeda bioherms in the northern Great Barrier Reef - Zsanett Szilagyi; Luke Nothdurft; Stephanie Duce; Jody M. Webster; Mardi McNeil; Robin J. Beaman; Juan Carlos Braga; Trevor Graham; Maria Byrne; Amy Nau; Christopher Berry; Victorien Paumard; et al. (Geomorphology, 2026)

Photoperiod perturbations impact perfluorohexane sulfonate (PFHxS) induced developmental toxicity - Syed Rubaiyat Ferdous; Alfredo Rojas; Cole Frank; Yasmeen Berry; Heidi M. Sabatini; Xixia Luo; Sunil Sharma; Ryan Thummel; Christopher Chouinard; Subham Dasgupta (Journal of Hazardous Materials, 2026)

Archaeopteris trees at high southern latitudes in the late Devonian - Robert W. Gess; Christopher Berry (Review of Palaeobotany and Palynology, 2024)

Small molecule therapeutics for neutralising venom toxins – a drug discovery approach - Laura-Oana Albulescu; Adam Westhorpe; Amy Marriott; Rachel H. Clare; Emma Stars; Nada Mosallam; Daniel Chong-Jun-Weng; Ramachandran Gunasekar; Charlotte A. Dawson; Christopher Woodley; Nivya James; Rohit Patel; et al. (Toxicon, 2024)

Effects of agriculture and urbanization on the geochemistry of the Scioto River, Ohio - Connor M. Wichterich; Susan A. Welch; Christopher B. Gardner; Devin F. Smith; W. Berry Lyons (Applied Geochemistry, 2024)

Ocean acidification significantly alters the trace element content of the kelp, Saccharina latissima - Jack Schultz; Dianna L. Berry Gobler; Craig S. Young; Aleida Perez; Michael H. Doall; Christopher J. Gobler (Marine Pollution Bulletin, 2024)

Effects of a field-sprayed antibiotic on bee foraging behavior and pollination in pear orchards - Laura Avila; Christopher McCullough; Annie Schiffer; JoMari Moreno; Neha Ganjur; Zachary Ofenloch; Tianna DuPont; Louis Nottingham; Nicole M. Gerardo; Berry J. Brosi (Agriculture, Ecosystems & Environment, 2024)

Letter to the Editors regarding “10% body weight (gain) change as criterion for the maximum tolerated dose: A critical analysis” - Sir Colin L. Berry; Samuel M. Cohen; J. Christopher Corton; Joao Lauro Viana de Camargo; Gerhard Eisenbrand; Shoji Fukushima; Helmut Greim; Klaus Weber; Ivonne M.C.M. Rietjens; Christian Strupp (Regulatory Toxicology and Pharmacology, 2023)

Carbonate weathering, phosphate fertilizer, and hydrologic controls on dissolved uranium in rivers in the US Corn Belt: Disentangling seasonal geogenic- and fertilizer-derived sources - Christopher B. Gardner; Connor Wichterich; Adolfo E. Calero; Susan A. Welch; Elisabeth Widom; Devin F. Smith; Anne E. Carey; W. Berry Lyons (Science of The Total Environment, 2023)

Rebuilding A Collapsed Bivalve Population, Restoring Seagrass Meadows, and Eradicating Harmful Algal Blooms In A Temperate Lagoon Using Spawner Sanctuaries - Christopher J. Gobler; Michael H. Doall; Bradley J. Peterson; Craig S. Young; Flynn DeLaney; Ryan B. Wallace; Stephen J. Tomasetti; Timothy P. Curtin; Brooke K. Morrell; Elizabeth M. Lamoureux; Berry Ueoka; Andrew W. Griffith; et al. (Frontiers in Marine Science, 2022)
During the past century, bivalve populations across the globe have collapsed, resulting in negative ecosystem consequences due to their outsized impact on shallow estuaries. In response, there has been strong interest in the restoration of marine bivalve populations. Here, we present a decade-long restoration effort that sought to rebuild a collapsed (99.5% reduction in harvest) and recruitment-limited population of hard clams ( Mercenaria mercenaria ) in Shinnecock Bay, NY, USA, using spawner sanctuaries: no-harvest zones where adults were planted at high densities (~27 m- 2 ). Between 2012 to 2019, more than 3.2 million clams were planted in 64 discrete sanctuary plots (~1,850 m 2 each) located in zones with maximal larval retention and sediment and seawater characteristics that would maximize the conditioning and spawning of adults. Hydrodynamic models, quantification of hard clam larvae, and spatial recruitment patterns demonstrated larvae spawned within sanctuaries were transported to regions where clam densities significantly increased 18-fold over seven years (2015-2021; p <0.001) and harvests significantly increased more than 16-fold over nine years (2012-2021; p <0.0001). Increases in populations and harvests were caused by smaller clams recruited within the time frame of the creation of spawner sanctuaries. Higher clam densities caused biological filtration times of the bay to decrease from up to three months at the start of the project to as low as 10 days in 2021. Concurrently, concentrations of the harmful brown tide alga, Aureococcus anophagefferens , and chlorophyll a significantly decreased ( p <0.005) while water clarity and the extent of seagrass beds significantly increased ( p <0.05). Increases in clam landings and improvements in water quality were not observed in adjacent lagoonal estuaries where restoration did not occur. Given these outcomes and the global need for rebuilding marine life, the implementation of spawner sanctuaries using the criteria set forth herein may be a promising approach for restoring hard clam and other bivalve populations in estuaries elsewhere.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Representing plant diversity in land models: An evolutionary approach to make “Functional Types” more functional - Leander D. L. Anderegg; Daniel M. Griffith; Jeannine Cavender‐Bares; William J. Riley; Joseph A. Berry; Todd E. Dawson; Christopher J. Still (Global Change Biology, 2022)
Plants are critical mediators of terrestrial mass and energy fluxes, and their structural and functional traits have profound impacts on local and global climate, biogeochemistry, biodiversity, and hydrology. Yet, Earth System Models (ESMs), our most powerful tools for predicting the effects of humans on the coupled biosphere–atmosphere system, simplify the incredible diversity of land plants into a handful of coarse categories of “Plant Functional Types” (PFTs) that often fail to capture ecological dynamics such as biome distributions. The inclusion of more realistic functional diversity is a recognized goal for ESMs, yet there is currently no consistent, widely accepted way to add diversity to models, that is, to determine what new PFTs to add and with what data to constrain their parameters. We review approaches to representing plant diversity in ESMs and draw on recent ecological and evolutionary findings to present an evolution‐based functional type approach for further disaggregating functional diversity. Specifically, the prevalence of niche conservatism, or the tendency of closely related taxa to retain similar ecological and functional attributes through evolutionary time, reveals that evolutionary relatedness is a powerful framework for summarizing functional similarities and differences among plant types. We advocate that Plant Functional Types based on dominant evolutionary lineages (“Lineage Functional Types”) will provide an ecologically defensible, tractable, and scalable framework for representing plant diversity in next‐generation ESMs, with the potential to improve parameterization, process representation, and model benchmarking. We highlight how the importance of evolutionary history for plant function can unify the work of disparate fields to improve predictive modeling of the Earth system.

Targeting Tau Mitigates Mitochondrial Fragmentation and Oxidative Stress in Amyotrophic Lateral Sclerosis - Tiziana Petrozziello; Evan A. Bordt; Alexandra N. Mills; Spencer E. Kim; Ellen Sapp; Benjamin A. Devlin; Abigail A. Obeng-Marnu; Sali M. K. Farhan; Ana C. Amaral; Simon Dujardin; Patrick M. Dooley; Christopher Henstridge; et al. (Molecular Neurobiology, 2022)

The limiting factors and regulatory processes that control the environmental responses of C3, C3–C4 intermediate, and C4 photosynthesis - Jennifer E. Johnson; Christopher B. Field; Joseph A. Berry (Oecologia, 2021)
Here, we describe a model of C 3 , C 3 –C 4 intermediate, and C 4 photosynthesis that is designed to facilitate quantitative analysis of physiological measurements. The model relates the factors limiting electron transport and carbon metabolism, the regulatory processes that coordinate these metabolic domains, and the responses to light, carbon dioxide, and temperature. It has three unique features. First, mechanistic expressions describe how the cytochrome b 6 f complex controls electron transport in mesophyll and bundle sheath chloroplasts. Second, the coupling between the mesophyll and bundle sheath expressions represents how feedback regulation of Cyt b 6 f coordinates electron transport and carbon metabolism. Third, the temperature sensitivity of Cyt b 6 f is differentiated from that of the coupling between NADPH, Fd, and ATP production. Using this model, we present simulations demonstrating that the light dependence of the carbon dioxide compensation point in C 3 –C 4 leaves can be explained by co-occurrence of light saturation in the mesophyll and light limitation in the bundle sheath. We also present inversions demonstrating that population-level variation in the carbon dioxide compensation point in a Type I C 3 –C 4 plant, Flaveria chloraefolia , can be explained by variable allocation of photosynthetic capacity to the bundle sheath. These results suggest that Type I C 3 –C 4 intermediate plants adjust pigment and protein distributions to optimize the glycine shuttle under different light and temperature regimes, and that the malate and aspartate shuttles may have originally functioned to smooth out the energy supply and demand associated with the glycine shuttle. This model has a wide range of potential applications to physiological, ecological, and evolutionary questions.

The EU chemicals strategy for sustainability: in support of the BfR position - Frank A. Barile; Sir Colin Berry; Bas Blaauboer; Alan Boobis; Herrmann M. Bolt; Christopher Borgert; Wolfgang Dekant; Daniel Dietrich; Jose L. Domingo; Corrado L. Galli; Gio Batta Gori; Helmut Greim; et al. (Archives of Toxicology, 2021)
The EU chemicals strategy for sustainability (CSS) asserts that both human health and the environment are presently threatened and that further regulation is necessary. In a recent Guest Editorial, members of the German competent authority for risk assessment, the BfR, raised concerns about the scientific justification for this strategy. The complexity and interdependence of the networks of regulation of chemical substances have ensured that public health and wellbeing in the EU have continuously improved. A continuous process of improvement in consumer protection is clearly desirable but any initiative directed towards this objective must be based on scientific knowledge. It must not confound risk with other factors in determining policy. This conclusion is fully supported in the present Commentary including the request to improve both, data collection and the time-consuming and bureaucratic procedures that delay the publication of regulations.

Transcriptomic Responses of Four Pelagophytes to Nutrient (N, P) and Light Stress - Yoonja Kang; Matthew J. Harke; Dianna L. Berry; Jackie L. Collier; Steven W. Wilhelm; Sonya T. Dyhrman; Christopher J. Gobler (Frontiers in Marine Science, 2021)
Pelagophytes are abundant picophytoplankton within open ocean ecosystems and the causative algae of harmful brown tide blooms in estuaries. The physiological capabilities facilitating the ecological success of pelagophytes in these diverse ecosystems remains poorly understood. Here, we investigated the transcriptional response of two coastal pelagophytes ( Aureococcus anophagefferens and Aureoumbra lagunensis ) and two open ocean pelagophytes ( Pelagococcus subviridis and Pelagomonas calceolata ) to conditions commonly found within the marine ecosystems where they thrive: low concentrations of nitrogen (N), phosphorus (P), or light. OrthoMCL was used to generate a total of 62,653 orthologous groups (OGs) with only a small fraction of these OGs (2,776 or 4.4%) being shared among all four pelagophytes. Of the commonly shared OGs, 8% were significantly differentially abundant under low N, P, or light with the majority associated with energy and lipid metabolism. Distinct responses among pelagophytes included increased abundance of transcripts encoding phosphate transporters ( Aureococcus ) and transcripts encoding a pyrophosphatase ( Aureococcus and Pelagomonas ) under low P, the expression of a suite of organic nitrogen-degrading enzymes under low N ( Aureoumbra and Pelagomonas ), increased abundance of transcripts encoding flavodoxins relative to ferredoxins ( Pelagomonas ) and transcripts encoding lysophospholipase ( Pelagococcus ) under low light, and both increases and decreases in abundance of transcripts encoding selenoproteins in all pelagophytes except Pelagococcus . Collectively, this study provides new information on the expressed gene compliment of these poorly characterized taxa and demonstrates that these pelagophytes possess a combination of shared and unique physiological features that likely facilitate their adaptation to distinct environmental conditions.

Human exposure to synthetic endocrine disrupting chemicals (S-EDCs) is generally negligible as compared to natural compounds with higher or comparable endocrine activity: how to evaluate the risk of the S-EDCs? - Herman Autrup; Frank A. Barile; Sir Colin Berry; Bas J. Blaauboer; Alan Boobis; Herrmann Bolt; Christopher J. Borgert; Wolfgang Dekant; Daniel Dietrich; Jose L. Domingo; Gio Batta Gori; Helmut Greim; et al. (Archives of Toxicology, 2020)
Theoretically, both synthetic endocrine disrupting chemicals (S-EDCs) and natural (exogenous and endogenous) endocrine disrupting chemicals (N-EDCs) can interact with endocrine receptors and disturb hormonal balance. However, compared to endogenous hormones, S-EDCs are only weak partial agonists with receptor affinities several orders of magnitude lower. Thus, to elicit observable effects, S-EDCs require considerably higher concentrations to attain sufficient receptor occupancy or to displace natural hormones and other endogenous ligands. Significant exposures to exogenous N-EDCs may result from ingestion of foods such as soy-based diets, green tea and sweet mustard. While their potencies are lower as compared to natural endogenous hormones, they usually are considerably more potent than S-EDCs. Effects of exogenous N-EDCs on the endocrine system were observed at high dietary intakes. A causal relation between their mechanism of action and these effects is established and biologically plausible. In contrast, the assumption that the much lower human exposures to S-EDCs may induce observable endocrine effects is not plausible. Hence, it is not surprising that epidemiological studies searching for an association between S-EDC exposure and health effects have failed. Regarding testing for potential endocrine effects, a scientifically justified screen should use in vitro tests to compare potencies of S-EDCs with those of reference N-EDCs. When the potency of the S-EDC is similar or smaller than that of the N-EDC, further testing in laboratory animals and regulatory consequences are not warranted.

Yield reduction historically associated with the Aegilops ventricosa 7DV introgression is genetically and physically distinct from the eyespot resistance gene Pch1 - Marianna Pasquariello; Simon Berry; Christopher Burt; Cristobal Uauy; Paul Nicholson (Theoretical and Applied Genetics, 2020)
Key message Yield penalty and increased grain protein content traits associated with Aegilops ventricosa 7D introgression have been mapped for the first time, and they are physically distinct from the eyespot resistance locus Pch1. Abstract Wheat wild relatives represent an important source of genetic variation, but introgression of agronomically relevant genes, such as for disease resistance, may lead to the simultaneous introduction of genetically linked deleterious traits. Pch1 is a dominant gene, conferring resistance to eyespot and was introgressed to wheat from Aegilops ventricosa as part of a large segment of the 7D V chromosome. This introgression has been associated with a significant yield reduction and a concomitant increase in grain protein content. In this study, we evaluated both traits and their relationship to the location of the Pch1 gene. We found that both QTLs were clearly distinct from the Pch1 gene, being located on a different linkage group to Pch1 . In addition, we found that the QTL for increased grain protein content was strong and consistent across field trials, whereas the yield penalty QTL was unstable and environmentally dependent. The yield and grain protein content QTLs were genetically linked and located in the same linkage group. This finding is due in part to the small size of the population, and to the restricted recombination between wheat 7D and Ae. ventricosa 7D v chromosomes. Although recombination in this interval is rare, it does occur. A recombinant line containing Pch1 and 7D_KASP6 , the marker associated with increase in grain protein content, but not Xwmc221 , the marker associated with the yield penalty effect, was identified.

Precipitation mediates sap flux sensitivity to evaporative demand in the neotropics - Charlotte Grossiord; Bradley Christoffersen; Aura M. Alonso-Rodríguez; Kristina Anderson-Teixeira; Heidi Asbjornsen; Luiza Maria T. Aparecido; Z. Carter Berry; Christopher Baraloto; Damien Bonal; Isaac Borrego; Benoit Burban; Jeffrey Q. Chambers; et al. (Oecologia, 2019)

Terrestrial gross primary production: Using NIR V to scale from site to globe - Grayson Badgley; Leander D. L. Anderegg; Joseph A. Berry; Christopher B. Field (Global Change Biology, 2019)
Terrestrial photosynthesis is the largest and one of the most uncertain fluxes in the global carbon cycle. We find that near‐infrared reflectance of vegetation (NIR V ), a remotely sensed measure of canopy structure, accurately predicts photosynthesis at FLUXNET validation sites at monthly to annual timescales ( R 2 = 0.68), without the need for difficult to acquire information about environmental factors that constrain photosynthesis at short timescales. Scaling the relationship between gross primary production (GPP) and NIR V from FLUXNET eddy covariance sites, we estimate global annual terrestrial photosynthesis to be 147 Pg C/year (95% credible interval 131–163 Pg C/year), which falls between bottom‐up GPP estimates and the top‐down global constraint on GPP from oxygen isotopes. NIR V ‐derived estimates of GPP are systematically higher than existing bottom‐up estimates, especially throughout the midlatitudes. Progress in improving estimated GPP from NIR V can come from improved cloud screening in satellite data and increased resolution of vegetation characteristics, especially details about plant photosynthetic pathway.

Pazopanib may reduce bleeding in hereditary hemorrhagic telangiectasia - Marie E. Faughnan; James R. Gossage; Murali M. Chakinala; S. Paul Oh; Raj Kasthuri; Christopher C. W. Hughes; Justin P. McWilliams; Joseph G. Parambil; Nicholas Vozoris; Jill Donaldson; Gitanjali Paul; Pamela Berry; et al. (Angiogenesis, 2019)
Pazopanib (Votrient) is an orally administered tyrosine kinase inhibitor that blocks VEGF receptors potentially serving as anti-angiogenic treatment for hereditary hemorrhagic telangiectasia (HHT). We report a prospective, multi-center, open-label, dose-escalating study [50 mg, 100 mg, 200 mg, and 400 mg], designed as a proof-of-concept study to demonstrate efficacy of pazopanib on HHT-related bleeding, and to measure safety. Patients, recruited at 5 HHT Centers, required ≥ 2 Curacao criteria AND [anemia OR severe epistaxis with iron deficiency]. Co-primary outcomes, hemoglobin (Hgb) and epistaxis severity, were measured during and after treatment, and compared to baseline. Safety monitoring occurred every 1.5 weeks. Seven patients were treated with 50 mg pazopanib daily. Six/seven showed at least 50% decrease in epistaxis duration relative to baseline at some point during study; 3 showed at least 50% decrease in duration during Weeks 11 and 12. Six patients showed a decrease in ESS of > 0.71 (MID) relative to baseline at some point during study; 3/6 showed a sustained improvement. Four patients showed > 2 gm improvement in Hgb relative to baseline at one or more points during study. Health-related QOL scores improved on all SF-36 domains at Week 6 and/or Week 12, except general health (unchanged). There were 19 adverse events (AE) including one severe AE (elevated LFTs, withdrawn from dosing at 43 days); with no serious AE. In conclusion, we observed an improvement in Hgb and/or epistaxis in all treated patients. This occurred at a dose much lower than typically used for oncologic indications, with no serious AE. Further studies of pazopanib efficacy are warranted.

Constraints on oxygen fugacity within metal capsules - Ulrich H. Faul; Christopher J. Cline II; Andrew Berry; Ian Jackson; Gordana Garapić (Physics and Chemistry of Minerals, 2018)

Performance of the Population Bioequivalence (PBE) Statistical Test Using an IPAC-RS Database of Delivered Dose from Metered Dose Inhalers - Beth Morgan; Stephanie Chen; David Christopher; Göran Långström; Christopher Wiggenhorn; Elise Burmeister Getz; Hayden Beresford; Thomas Hoffelder; Daniela Acerbi; Stephen Andrews; Mark Berry; Monisha Dey; et al. (AAPS PharmSciTech, 2018)

Clinical Phenotype of Adult Fragile X Gray Zone Allele Carriers: a Case Series - Sarah M. Debrey; Maureen A. Leehey; Olga Klepitskaya; Christopher M. Filley; Raj C. Shah; Benzi Kluger; Elizabeth Berry-Kravis; Elaine Spector; Flora Tassone; Deborah A. Hall (The Cerebellum, 2016)

The ability of the red macroalga, Porphyra purpurea (Rhodophyceae) to inhibit the proliferation of seven common harmful microalgae - Ying Zhong Tang; Yoonja Kang; Dianna Berry; Christopher J. Gobler (Journal of Applied Phycology, 2015)

Loss of whole-tree hydraulic conductance during severe drought and multi-year forest die-off - William R. L. Anderegg; Leander D. L. Anderegg; Joseph A. Berry; Christopher B. Field (Oecologia, 2014)

Photosynthetic gene expression in higher plants - James O. Berry; Pradeep Yerramsetty; Amy M. Zielinski; Christopher M. Mure (Photosynthesis Research, 2013)

Meta-analyses of colorectal cancer risk factors - Constance M. Johnson; Caimiao Wei; Joe E. Ensor; Derek J. Smolenski; Christopher I. Amos; Bernard Levin; Donald A. Berry (Cancer Causes & Control, 2013)

Drought's legacy: multiyear hydraulic deterioration underlies widespread aspen forest die‐off and portends increased future risk - William R. L. Anderegg; Lenka Plavcová; Leander D. L. Anderegg; Uwe G. Hacke; Joseph A. Berry; Christopher B. Field (Global Change Biology, 2013)
Forest mortality constitutes a major uncertainty in projections of climate impacts on terrestrial ecosystems and carbon‐cycle feedbacks. Recent drought‐induced, widespread forest die‐offs highlight that climate change could accelerate forest mortality with its diverse and potentially severe consequences for the global carbon cycle, ecosystem services, and biodiversity. How trees die during drought over multiple years remains largely unknown and precludes mechanistic modeling and prediction of forest die‐off with climate change. Here, we examine the physiological basis of a recent multiyear widespread die‐off of trembling aspen ( P opulus tremuloides ) across much of western N orth A merica. Using observations from both native trees while they are dying and a rainfall exclusion experiment on mature trees, we measure hydraulic performance over multiple seasons and years and assess pathways of accumulated hydraulic damage. We test whether accumulated hydraulic damage can predict the probability of tree survival over 2 years. We find that hydraulic damage persisted and increased in dying trees over multiple years and exhibited few signs of repair. This accumulated hydraulic deterioration is largely mediated by increased vulnerability to cavitation, a process known as cavitation fatigue. Furthermore, this hydraulic damage predicts the probability of interyear stem mortality. Contrary to the expectation that surviving trees have weathered severe drought, the hydraulic deterioration demonstrated here reveals that surviving regions of these forests are actually more vulnerable to future droughts due to accumulated xylem damage. As the most widespread tree species in N orth A merica, increasing vulnerability to drought in these forests has important ramifications for ecosystem stability, biodiversity, and ecosystem carbon balance. Our results provide a foundation for incorporating accumulated drought impacts into climate–vegetation models. Finally, our findings highlight the critical role of drought stress accumulation and repair of stress‐induced damage for avoiding plant mortality, presenting a dynamic and contingent framework for drought impacts on forest ecosystems.

Understanding age‐specific dispersal in fishes through hydrodynamic modelling, genetic simulations and microsatellite DNA analysis - OLIVER BERRY; PHILLIP ENGLAND; ROSS J. MARRIOTT; CHRISTOPHER P. BURRIDGE; STEPHEN J. NEWMAN (Molecular Ecology, 2012)
Many marine species have vastly different capacities for dispersal during larval, juvenile and adult life stages, and this has the potential to complicate the identification of population boundaries and the implementation of effective management strategies such as marine protected areas. Genetic studies of population structure and dispersal rarely disentangle these differences and usually provide only lifetime‐averaged information that can be considered by managers. We address this limitation by combining age‐specific autocorrelation analysis of microsatellite genotypes, hydrodynamic modelling and genetic simulations to reveal changes in the extent of dispersal during the lifetime of a marine fish. We focus on an exploited coral reef species, Lethrinus nebulosus , which has a circum‐tropical distribution and is a key component of a multispecies fishery in northwestern Australia. Conventional population genetic analyses revealed extensive gene flow in this species over vast distances (up to 1500 km). Yet, when realistic adult dispersal behaviours were modelled, they could not account for these observations, implying adult dispersal does not dominate gene flow. Instead, hydrodynamic modelling showed that larval L. nebulosus are likely to be transported hundreds of kilometres, easily accounting for the observed gene flow. Despite the vast scale of larval transport, juvenile L. nebulosus exhibited fine‐scale genetic autocorrelation, which declined with age. This implies both larval cohesion and extremely limited juvenile dispersal prior to maturity. The multidisciplinary approach adopted in this study provides a uniquely comprehensive insight into spatial processes in this marine fish.

Understanding Causes and Impacts of the Dinoflagellate, Cochlodinium polykrikoides, Blooms in the Chesapeake Bay - Margaret R. Mulholland; Ryan E. Morse; George E. Boneillo; Peter W. Bernhardt; Katherine C. Filippino; Leo A. Procise; Jose L. Blanco-Garcia; Harold G. Marshall; Todd A. Egerton; William S. Hunley; Kenneth A. Moore; Dianna L. Berry; et al. (Estuaries and Coasts, 2009)

Reduction of Petroleum Hydrocarbons and Toxicity in Refinery Wastewater by Bioremediation - Grażyna A. Płaza; Kamlesh Jangid; Krystyna Łukasik; Grzegorz Nałęcz-Jawecki; Christopher J. Berry; Robin L. Brigmon (Bulletin of Environmental Contamination and Toxicology, 2008)

Morphological diversity among fishes in a Great Plains river drainage - Christopher W. Hoagstrom; Charles R. Berry (Hydrobiologia, 2008)

Utilization of monocyclic aromatic hydrocarbons individually and in mixture by bacteria isolated from petroleum-contaminated soil - Grażyna A. Płaza; Jacek Wypych; Christopher Berry; Robin L. Brigmon (World Journal of Microbiology and Biotechnology, 2007)

18 O composition of CO 2 and H 2 O ecosystem pools and fluxes in a tallgrass prairie: Simulations and comparisons to measurements - William J. Riley; Christopher J. Still; Brent R. Helliker; Miguel Ribas‐Carbo; Joseph A. Berry (Global Change Biology, 2003)
In this paper we describe measurements and modeling of 18 O in CO 2 and H 2 O pools and fluxes at a tallgrass prairie site in Oklahoma. We present measurements of the δ 18 O value of leaf water, depth‐resolved soil water, atmospheric water vapor, and Keeling plot δ 18 O intercepts for net soil‐surface CO 2 and ecosystem CO 2 and H 2 O fluxes during three periods of the 2000 growing season. Daytime discrimination against C 18 OO, as calculated from measured above‐canopy CO 2 and δ 18 O gradients, is also presented. To interpret the isotope measurements, we applied an integrated land‐surface and isotope model (ISOLSM) that simulates ecosystem H 2 18 O and C 18 OO stocks and fluxes. ISOLSM accurately predicted the measured isotopic composition of ecosystem water pools and the δ 18 O value of net ecosystem CO 2 and H 2 O fluxes. Simulations indicate that incomplete equilibration between CO 2 and H 2 O within C 4 plant leaves can have a substantial impact on ecosystem discrimination. Diurnal variations in the δ 18 O value of above‐canopy vapor had a small impact on the predicted δ 18 O value of ecosystem water pools, although sustained differences had a large impact. Diurnal variations in the δ 18 O value of above‐canopy CO 2 substantially affected the predicted ecosystem discrimination. Leaves dominate the ecosystem 18 O‐isoflux in CO 2 during the growing season, while the soil contribution is relatively small and less variable. However, interpreting daytime measurements of ecosystem C 18 OO fluxes requires accurate predictions of both soil and leaf 18 O‐isofluxes.

The contribution of C 3 and C 4 plants to the carbon cycle of a tallgrass prairie: an isotopic approach - Christopher J. Still; Joseph A. Berry; Miquel Ribas-Carbo; Brent R. Helliker (Oecologia, 2003)

Introduction - Joseph A. Berry; Christopher B. Field; Arthur R. Grossman (Photosynthesis Research, 2001)

Growth and lactic acid production in batch culture of Lactobacillus rhamnosus in a defined medium - Andrew R. Berry; Christopher M.M. Franco; Wei Zhang; Anton P.J. Middelberg (Biotechnology Letters, 1999)

Microbiology of Spent Nuclear Fuel Storage Basins - Jorge W. Santo Domingo; Christopher J. Berry; Michael Summer; Carl B. Fliermans (Current Microbiology, 1998)